Case Report: Abomasum Impaction in Beef Cattle Due to High Intake of Distillers' Grain and Treatment Options in Southwest China - Yong, Kang; Luo, Zhengzhong; Yang, Qinwen; Zhang, Chuanshi; Zhou, Qianlan; Jiang, Hua; Zhang, Yong; Cao, Suizhong (Frontiers in Veterinary Science, 2021)
In Southern China, distillers’ grain is the main feed ingredient for small beef cattle farms. High intake of distillers’ grain may lead to abomasum impaction, a disorder caused by the accumulation of solid content within the organ. For treatment, there are non-surgical and surgical options. In this study, we aimed to describe the clinical presentation, diagnosis, and treatment of beef cattle with abomasum impaction due to high intake of distillers’ grain. Forty-nine Simmental beef cattle from 13 farms in Chongqing, China, were diagnosed with abomasum impaction. Animals were male, aged ≤ 2 years, and weighed between 200 and 350 kg. In this retrospective study, information on distillers’ grain intake and clinical data were collected for 49 beef cattle diagnosed with abomasum impaction. The animals were treated between 2011 and 2019 with either non-surgical therapy or surgery. Animals diagnosed with mild abomasum impaction (n = 14) fully recovered after non-surgical treatment. Among moderate cases (n = 19), 12 cattle recovered after non-surgical treatment (63%), while the remaining seven did not respond well and underwent surgery. Three of those animals were subsequently cured (3/7). Among the severe cases (n = 16), four cattle were cured after non-surgical treatment (25%) (4/16). Of the remaining 12 cattle, six were slaughtered, and six died after surgery. Non-surgical treatment is efficient for mild abomasum impaction caused by a high intake of distillers’ grain and may be considered for both moderate and severe cases. However, the treatment success rate for more severe cases decreases as the disease severity worsens.